1990
DOI: 10.1002/app.1990.070410939
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐active agents based on propoxylated lignosulfonate

Abstract: SynopsisA commercial lignosulfonate was modified by the addition of propylene oxide. The products obtained had a degree of propoxylation ranging from 19% to 49%. The modified lignosulfonates retained high solubility in water and high salinity tolerance, while their interfacial activity increased dramatically in comparison with the original lignosulfonate. Aqueous solutions of propoxylated lignosulfonates exhibited very low interfacial tensions (down to 10-'-10-* m N / m ) against both a pure hydrocarbon (isooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…These surfactants have been reinvented and studied for other applications such as the ethoxylated sulfonates [149] to eliminate the co-surfactant requirement for petroleum sulfonates in microemulsions or to improve lignosulfonate tensioactivity and salt tolerance [150]. Highly branched Guerbert type propoxylated structures [151], as well as surfactants for systems containing chlorinated oils [152], were also proposed.…”
Section: Insensitivity To Surfactant Concentrationmentioning
confidence: 99%
“…These surfactants have been reinvented and studied for other applications such as the ethoxylated sulfonates [149] to eliminate the co-surfactant requirement for petroleum sulfonates in microemulsions or to improve lignosulfonate tensioactivity and salt tolerance [150]. Highly branched Guerbert type propoxylated structures [151], as well as surfactants for systems containing chlorinated oils [152], were also proposed.…”
Section: Insensitivity To Surfactant Concentrationmentioning
confidence: 99%
“…19 It has been reported that lignin can react with an alkene oxide to yield lignin-based polyol, which in turn improves the solubility and uniformity of lignin. 18,20 Chemically modified lignins provide several advantages in replacing conventional polyols used in polyurethane fabrication. During lignin modification, the majority of phenolic hydroxyl groups are converted to aliphatic hydroxyl units, leading to readily available and more reactive hydroxyl groups.…”
Section: ' Introductionmentioning
confidence: 99%
“…pH 12.0) of ligninsulfonates with an alkene oxide, preferably propylene oxide. The reaction has been described repeatedly (Wu and Glasser 1984;Hornof and Hombek 1990).The product formed may be isolated by precipitation from a non-solvent, or it may be subjected directly to ion exchange. The complete protection of all phenolic hydroxyl groups is conveniently ascertained by difference-UVspectroscopy.…”
Section: Homogeneous Phase Etherification (Water-soluble Ionic Ethers)mentioning
confidence: 99%
“…These acylation procedures were mainly based on the use of water-swollen ligninsulfonates in pyridine prepared by elaborate and complex solvent exchange procedures. In addition to water-soluble ligninsulfonate esters, hydroxypropyl ethers of ligninsulfonate have also been reported recently (Hornof and Hombek 1990). Phenolic substances may conveniently be reacted with propylene oxide (and other alkene oxides) in cold aqueous alkaline solutions.…”
Section: Introductionmentioning
confidence: 98%